The Bacillus subtilis Acyl Lipid Desaturase Is a Δ5 Desaturase - Altabe, Silvia G. (American Society for Microbiology, 2003)
Bacillus subtilis was recently reported to synthesize unsaturated fatty acids (UFAs) with a double bond at positions Δ5, Δ7, and Δ9 (M. H. Weber, W. Klein, L. Muller, U. M. Niess, and M. A. Marahiel, Mol. Microbiol. 39:1321-1329, 2001). Since this finding would have considerable importance in the double-bond positional specificity displayed by the B. subtilis acyl lipid desaturase, we have attempted to confirm this observation. We report that the double bond of UFAs synthesized by B. subtilis is located exclusively at the Δ5 position, regardless of the growth temperature and the length chain of the fatty acids.